Taxonomic study of a new species of sap sucking mite (Acari:‎Eriophyidae) found on a medicinal plant- Mitragyna parvifolia ‎‎(roxb.) Korth (rubiaceae) from Indo-Gangetic plain of India - Sarkar‎, Sanjay (International Journal of Biological Research, 2025)
During general surveys for eriophyoid mites in the Indo-Gangetic Plain of India, a new species, Abacarus indogangeticus n. sp. of the family Eriophyidae, was found on the ventral and dorsal surfaces of the leaves of Mitragyna parvifolia (Roxb.). Korth (Rubiaceae). Mitragyna parvifolia is a medium to large deciduous tree, and it is recommended in Ayurveda for the prevention and treatment of many health ‎issues. After a thorough study, this mite species appears to be new to science, so the morphometric and diagnostic features of this new mite species are well described and illustrated from the area of the present study. A brief discussion on the genus Abacarus and the relationships of new species with other eriophyoid species is also provided. This new mite species causes damage to this economically important medicinal plant by ‎its sap sucking habit and produces leaf rusting and brown patches on leaves as visible damage symptom. Due to the infestation of this mite, the ‎leaves become unsuitable for medicinal use. The etymology of the new name of the mite is mentioned here. The holotype and paratype ‎specimens are deposited in a national repository, and registration of new species in the Zoo-Bank Account is done following the International ‎Code of Zoological Nomenclature. For proper control and eradication of the mite pest, the taxonomic study of this mite and their relation to the host plant is very much essential‎.